Chattering reduction in step down converter using robust reaching law - Sridhara Somaguddu Ningappa; Siddesh Kondapur Basavarajan; Sudharashan Mungasavalli Katappa; Sandeep Velur Ramareddy; Lavakumar Tavane Basavarajappa (Bulletin of Electrical Engineering and Informatics, 2022)
The proposed robust reaching law for sliding mode control is used for chattering suppression, minimization of steady state error and reaching speed kept fast. With fine tuning parameters of robust reaching law, the system state reaches the sliding mode at the earliest. The mathematical analysis of the proposed reaching law is verifed. In one hand, they guarantee the system states reaches the sliding surface quickly and remain on it, in another way it deteriorate the chattering effectively, even unmatched certainties and disturbances. Such that the system response can better realize the unification of rapidity. A proposed reaching law applied to SMC DC-DC step down converter to analyse the chattering, it reduces the switching losses in the switching devices of the step down converter. In turn efficiency of the buck converter increases. MATLAB/Simulink results gives significant turn down of chattering and dynamic response of the system. This research work effectively improves the performance of the system.